2007 IEEE International Workshop on Haptic, Audio and Visual Environments and Games 2007
DOI: 10.1109/have.2007.4371580
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors for Designing a Haptic Interface for Interaction with a Virtual Environment

Abstract: Designing haptic displays is one of the main challenges in force sensitivity are obtained for a user engaged in a task that creating virtual reality systems with the sense of touch. The design of is similar to Fitt's task [3] in a virtual environment. The effects the hardware and software of haptic interfaces depends critically on of force direction and the increment/decrement of the forces on the capabilities of the human haptic system. For example, force feed-force JND are also studied. back interfaces, due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In all these applications, unlike previous research, the motion of a user's hand and the virtual haptic object is important. The result in [16,11,31,30] shows a significant variation in human perception and the force thresholds while the velocity of the subject's hand is changed, albeit in a different scenario than is studied in this paper.…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…In all these applications, unlike previous research, the motion of a user's hand and the virtual haptic object is important. The result in [16,11,31,30] shows a significant variation in human perception and the force thresholds while the velocity of the subject's hand is changed, albeit in a different scenario than is studied in this paper.…”
Section: Related Workmentioning
confidence: 96%
“…Zadeh et. al [30] derived Just Noticeable Differences (JND) for human force sensing. They found that the effect of force direction on the force JND is dependent on the increasing or decreasing of the force.…”
Section: Related Workmentioning
confidence: 99%
“…Because of these constraints, mobile devices could benefit from special considerations when accessing information over the Internet. In fact, there is a major issue with rendering web content on mobile devices [12], which leads to a low web browsing QoE of the end user.…”
Section: B Mobile Web Qoe (Mwqoe)mentioning
confidence: 99%
“…Many studies exist which investigate human motor and sensory performance. Stocco and Salcudean surveyed human hand capabilities to inform haptic interface design [10] while others have tested maximum hand torque [11] or just-noticeable-differences (JND) in force [12]. Of particular interest are the visual-motor response time (RT), frequency response of the hand, and accuracy in positioning and force exertion.…”
Section: Introductionmentioning
confidence: 99%